The voice of science on climate change in the mainstream Turkish press - Uzelgun, M. A. (2015)
This study aims to explore how the Turkish press represents the discourse of climate change scientists. This is achieved by analyzing climate change-related articles that quote scientists, directly and indirectly, in two Turkish mainstream newspapers (N = 132, 7 years). The Turkish case illustrates how scientific rhetoric is used for presenting climate change as a matter of concern in an industrializing country. The analysis suggests that climate science is portrayed as an un-discussed authority. News articles rely on data about the disturbance of species and the state of the natural environment to provide proof of global warming, by which they produce an implicit moral imperative. The articles also portray the worst threats and challenges—those pertaining to human society—as residing mostly in the future. We conclude by discussing the implications of the use of a projected future to convey a discourse emphasizing the alarming risks associated with climate change.